Equestrian Cultures in Global and Local Contexts - Adelman, Miriam; Thompson, Kirrilly (Springer International Publishing : Imprint: Springer, 2017)
This edited volume demonstrates the broader socio-cultural context for individual human-horse relations and equestrian practices by documenting the international value of equines; socially, culturally, as subjects of academic study and as drivers of public policy. It broadens our understanding of the importance of horses to humans by providing case studies from an unprecedented diversity of cultures. The volume is grounded in the contention that the changing status of equines reveals - and moves us to reflect on - important material and symbolic societal transformations ushered in by (post)modernity which affect local and global contexts alike. Through a detailed consideration of the social relations and cultural dimensions of equestrian practices across several continents, this volume provides readers with an understanding of the ways in which interactions with horses provide global connectivity with localized identities, and vice versa. It further discusses new frontiers in the research on and practice of equestrianism, framed against global megatrends and local micro-trends.